Customer behavior impact on international tourist's travel intention due to Covid-19 - Febriana Riestyaningrum; Ehsan Ferdaos; Bahruz Bayramov (Goodwood Publishing, 2020)
Purpose: Several industries affected by the Covid-19 outbreak – one of the most affected is the tourism industry due to travel restrictions, which have resulted in an unprecedented slump in the number of international tourists. This situation has an impact on changing consumer behavior towards intention to travel. This study aims to measure the impact of Covid-19 on international tourists' consumer behavior towards crises to intention to travel overseas after the pandemic is over. Research methodology: A paper questionnaire was distributed to international tourists who have been traveling abroad (outside country of origin) at least once during the last 12 months through a nonprobability, convenience-sampling approach. A total of 350 questionnaires were analyzed using multiple regression linear. Results: The results from the regression model suggest that: (1) general impact have significant partial effects on traveling intention; (2) attitude and preference have a significant partial impact to travel intention; (3) hygiene and safety have significant partial impacts to travel intention; (4) general impact, attitude, and preference, hygiene and safety have a significant simultaneous impact to travel intention. Implications and future research issues were discussed. Limitations: This research is limited due to the limited number of respondents. Contribution: This research suggests that every country carries out promotions and increases national branding to rebuild trust to travel. Keywords: Impact, Covid-19, Customer behavior, International tourists, Travel intention, Post-pandemic